2019
DOI: 10.1021/acs.energyfuels.9b02201
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Fine Particulate Matter and Polycyclic Aromatic Hydrocarbons Emitted from Coal Combustion Processes

Abstract: Characteristics and emission factors of condensable particulate matter (CPM) and filterable particulate matter (FPM2.5) and polycyclic aromatic hydrocarbons (PAHs) (16 U.S. EPA PAHs and 15 + 1 EU PAHs) emitted from a coal-fired power plant (plant A) and a coal-fired boiler (plant B) in Taiwan were investigated via stack samplings. Removal efficiencies of CPM, FPM2.5, and PAHs achieved with baghouse (BH) + seawater flue gas desulfurization (SWFGD) were also evaluated for plant A. Results indicate that CPM conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Those boilers were all equipped with air pollution control devices (APCDs). The previously reported emission factors of total PAH species (including gas phase and particulate phase) for PC boilers are very low, in the range of 0.002 to 0.6 mg/kg [20,[45][46][47]. Our ΣPAHs emission factors from PC boilers for the particulate phase fall in the range of those values.…”
Section: Emission Factors Of Pm 25 -Bound Pahsmentioning
confidence: 40%
“…Those boilers were all equipped with air pollution control devices (APCDs). The previously reported emission factors of total PAH species (including gas phase and particulate phase) for PC boilers are very low, in the range of 0.002 to 0.6 mg/kg [20,[45][46][47]. Our ΣPAHs emission factors from PC boilers for the particulate phase fall in the range of those values.…”
Section: Emission Factors Of Pm 25 -Bound Pahsmentioning
confidence: 40%
“…Generally, these two pollutants are related to diesel vehicular emissions [46][47][48][49][50][51][52] whereas the petrol vehicle emissions are characterized by B[a]P and dibenzo[ah]anthracene emissions [53][54][55][56][57]. For coal combustion, the PAHs profiles are generally characterized by a high presence of fluoranthene, pyrene, phenanthrene and anthracene, to which the chrysene and the isomer of benzo[k]fluorantene are added [58][59][60][61]. Regarding marine emissions, for ships at the port both in mooring and maneuvering, the PAHs fingerprint is represented by naphthalene, phenanthrene, pyrene, fluorene, followed by acenaphthylene and acenaphthalene [62][63][64][65].…”
Section: Organic Fractionmentioning
confidence: 99%
“…In terms of CPM, nonfilterable particles exist in the vapor phase before being discharged from stack and condense to fine particulate substances (aerodynamic diameter less than 2.5 μm) after cooling in the plume. ,− In fact, total particulate matter (TPM) emissions should be the sum of FPM and CPM. Several previous studies stated that CPM emissions represented the predominant contributors to TPM emissions based on field tests; final TPM emissions will be severely underestimated if CPM is not considered. Corio and Sherwell pointed out that the proportion of CPM in PM 10 emitted from coal-fired boilers was 76%, and the results conducted by Zheng et al showed that CPM accounted for 76.73% in TPM.…”
Section: Introductionmentioning
confidence: 99%